2020
DOI: 10.29312/remexca.v11i1.2207
|View full text |Cite
|
Sign up to set email alerts
|

Identificación de elementos discriminatorios para caracterizar el Coffea arabica L. empleando componentes principales

Abstract: La evaluación de la calidad en taza en agrosistemas de Coffea arabica L. es necesaria para generar alternativas que aseguren la calidad y diferenciación del café en Coatepec, Veracruz, México. El presente estudio se realizó con el objetivo de evaluar la calidad física y sensorial de las variedades Typica y Mundo Novo a través del análisis de componentes principales, durante el período 2017-2018, para identificar las variables que se asocian a la calidad en taza de las variedades. Once muestras de café cereza s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This argument favored the protection of coffee associated with its origin (Avelino et al, 2005), which has generated national and international recognition through the appellation of origin granted to Veracruz in 2000 and Chiapas in 2003 Pérez, 2012), creating not only value for producers in those regions, but also shaping the strategies for sourcing and distributing the coffee production chain (Conley;Wilson, 2018). In this context, although in Mexico several options have been promoted and developed to increase the profitability of the crop, such as organic coffee, fair trade, the denomination of coffee origin, and specialty coffees (Pérez-Portilla et al, 2005;Toledo;Moguel, 2012;Escamilla-Prado et al, 2015), the truth is that few studies have been published to specifically explain the factors related to the quality of coffee (Sánchez et al, 2018;Buendía-Espinoza et al, 2020). However, some important aspects have been identified, such as that the increase in the average annual temperature negatively influences the size of the grain, as well as the aroma and acidity of the beverage (Sánchez et al, 2018) and in general in the sensory attributes (Pérez-Portilla et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This argument favored the protection of coffee associated with its origin (Avelino et al, 2005), which has generated national and international recognition through the appellation of origin granted to Veracruz in 2000 and Chiapas in 2003 Pérez, 2012), creating not only value for producers in those regions, but also shaping the strategies for sourcing and distributing the coffee production chain (Conley;Wilson, 2018). In this context, although in Mexico several options have been promoted and developed to increase the profitability of the crop, such as organic coffee, fair trade, the denomination of coffee origin, and specialty coffees (Pérez-Portilla et al, 2005;Toledo;Moguel, 2012;Escamilla-Prado et al, 2015), the truth is that few studies have been published to specifically explain the factors related to the quality of coffee (Sánchez et al, 2018;Buendía-Espinoza et al, 2020). However, some important aspects have been identified, such as that the increase in the average annual temperature negatively influences the size of the grain, as well as the aroma and acidity of the beverage (Sánchez et al, 2018) and in general in the sensory attributes (Pérez-Portilla et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, varieties influence the flavor in cup (particularly those of Arabica type), determining their body, which is key to quality differentiation and therefore market success (Läderach et al, 2011;Figueroa-Hernández;Pérez-Soto;Godínez-Montoya, 2015;Luna-González et al, 2019). In addition, cultural practices (nutrition, pest and disease control), plant age, coffee pruning, shade regulation, weed control, and the production system have been considered to be an important factor in the attributes of the beverage (Rosas-Arellano et al, 2008), so it can be concluded that the quality of coffee in Mexico is the sum of the processes and management carried by the crop, pre, and post-harvest (Läderach et al, 2011;Buendía-Espinoza et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the results of the sensory analysis of the samples of ripe coffee beans (optimum) selected by the prototype, had higher averages of 84 points according to the SCAA standard, reflecting improvements with respect to the 82 points normally obtained in the Valle Grande Association with the traditional selection process. According to Buendía-Espinoza et al (2020), ensuring the quality of coffee requires standardizing and guaranteeing the selection of ripe or optimal beans that are considered special when processed, an action that the prototype helps to contribute to the Association by reducing selection time, labor and cost optimization.…”
Section: /7mentioning
confidence: 99%
“…The Valle Grande Association in the Alto Mayo area, in the province of Moyobamba, has a low production of specialty coffees, with cup quality averages of less than or equal to 83 points according to the sensory evaluation method of the Specialty Coffee Association of America (SCAA) according to the association expert cupper. This does not allow it to be competitive in the market and achieve better prices because, as indicated by Buendía-Espinoza et al (2020), cup quality is necessary to generate alternatives that ensure the quality and differentiation of coffee. One factor that causes this is the manual selection process of cherry coffee, with a high degree of subjectivity and error (Rosas-Echevarría et al, 2019), reaching 15.0% over-ripe beans, 2.0% dry beans, and 3.0% green beans.…”
Section: Introductionmentioning
confidence: 99%